2022
DOI: 10.3389/fbioe.2022.913839
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Bioactive Compounds in Oyster Shell and Tissues

Abstract: Oysters are saltwater bivalves with high nutritional and medicinal value that are consumed widely around the world. As well as being highly nutritious, oysters are a low-calorie, low-cholesterol source of protein and an exceptional source of zinc, which strengthens the immune system; and a rich source of bioactive compounds, which comprise various biological activities. The present review summarizes the biological applications and bioactive compounds from oyster shells, whole tissue, gill tissue, and mantle ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…30 A previous review clearly showed that bioactive peptides obtained from the whole, mantle, and gill tissues of oysters exhibit antioxidant, antimicrobial, antihypertensive, anticancer, antifatigue, anticoagulant, and anti-wrinkle effects, as well as enhancing osteoblast differentiation. 31 In this study, mixed oyster peptides were prepared by the combination of several enzymes. The composition of the mixed peptide was analyzed by MALDI-TOF/TOF, and the dominant peptide was determined.…”
Section: Discussionmentioning
confidence: 99%
“…30 A previous review clearly showed that bioactive peptides obtained from the whole, mantle, and gill tissues of oysters exhibit antioxidant, antimicrobial, antihypertensive, anticancer, antifatigue, anticoagulant, and anti-wrinkle effects, as well as enhancing osteoblast differentiation. 31 In this study, mixed oyster peptides were prepared by the combination of several enzymes. The composition of the mixed peptide was analyzed by MALDI-TOF/TOF, and the dominant peptide was determined.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zn-chelating peptides extracted from oysters have attracted wide attention [ 64 , 83 ]. Oysters are considered one of the richest food sources for Zn.…”
Section: Zinc Encapsulation and Chelation As Novel Approaches To Incr...mentioning
confidence: 99%
“…A cyclic heptapeptide, mollamide B (Figure 5), isolated from the colonial tunicate Didemnum molle indicated cytotoxicity against HIV-1 in human PBMCs at an EC50 value of 48.7 μM [142]. Two peptides, P1 and P2 [sequences LLEYSI (P1), and LLEYSL (P2)] have been isolated from the oyster (Crassostrea gigas) proteins hydrolysate prepared with thermolysin and have exhibited competitive HIV-1 protease inhibition activity (IC50 values of 20 and 15 nM, respectively, and Ki values of 13 and 10 nM, respectively) [143][144][145]. Clavanin B (peptide sequence: VFQFLGRIIHHVGNFVHGFSHVF), an alpha-helical peptide isolated from the tunicate Styela clava also exhibited anti-HIV activity with an EC50 value of 7.1 μM, TC50 value of 37.1 μM, and TI of >5.18 [146,147].…”
Section: Marine Mussels Ascidians and Oyster-derived Bioactive Peptid...mentioning
confidence: 99%